“Trap Door Flap”: Utility in the Treatment of Cutaneous Cystic Lesions: “Retalho em Alçapão”: Utilidade no Tratamento de Lesões Quísticas da Pele - Tavares, Ermelindo; Marques, Maria São José (Gazeta Médica, 2019)
INTRODUCTION: Epidermoid and pilar cysts are common benign subcutaneous lesions usually seen on the head and trunk. Surgery, when indicated, is the treatment of choice. For surgical resection several techniques can be used. The “trap door flap” is a technique that allows direct and complete visualization of the cyst and saving adjacent tissue. CASE REPORTS: Two patients (one male and one female) were submitted to excision of facial epidermoid cysts, under local anesthesia, followed by “trap door flap”. There were no postoperative complications. The cosmetics results were very acceptable. CONCLUSION: The “trap door flap” is a simple, safe and quickly performed procedure, being an excellent option to many classical surgical techniques.